Reducing CO2 emissions by targeting the world’s hyper-polluting power plants - Don Grant; David Zelinka; Stefania Mitova (Environmental Research Letters, 2021)
Combusting fossil fuels to produce electricity is the single largest contributor to sector-level, anthropogenic carbon pollution. Because sector-wide policies are often too unwieldy to implement, however, some researchers have recommended reducing electricity-based CO _2 emissions by targeting the most extreme emitters of each nation’s electricity industry. Here, we use a unique international data source to measure national disproportionalities in power plant CO _2 emissions and estimate the fraction of each country’s electricity-based CO _2 emissions that would be reduced if its most profligate polluters lowered their emission intensities, switched to gas fuels, and incorporated carbon capture and storage systems. We find that countries’ disproportionalities vary greatly and have mostly grown over time. We also find that 17%–49% of the world’s CO _2 emissions from electricity generation could be eliminated depending on the intensity standards, fuels, or carbon capture technologies adopted by hyper-emitting plants. This suggests that policies aimed at improving the environmental performance of ‘super polluters’ are effective strategies for transitioning to decarbonized energy systems.